2012
DOI: 10.1167/iovs.12-10271
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Protection via Modulation of the Amyloidogenic Pathway in Tumor Necrosis Factor–Induced Optic Neuropathy

Abstract: PURPOSE.To examine the changes in and localization of phosphorylated presenilin1 (p-PS1) and amyloid precursor protein (APP) in the optic nerve after intravitreal injection of TNF and to investigate the role of c-secretase in the cleavage of APP in optic nerve degeneration.METHODS. Groups of rats were euthanatized at 1 or 2 weeks after intravitreal injection of TNF. Levels of p-PS1 protein in the optic nerve were determined by immunoblotting and immunohistochemistry. The localization of APP was determined by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…It is also interesting to note that a recent study has demonstrated that glucose rescued cultured rat retinal cells from rotenone-induced toxicity via both the pentose phosphate pathway and the glycolytic pathway, with the maintenance of ATP levels and reduced reactive oxygen species production (Han et al, 2013 ). On the other hand, we previously found that astrocytes in the optic nerve were activated after TNF injection (Kojima et al, 2012 ). Therefore, one hypothesis is that TNF enhances glucose utilization by astrocytes and can perturb their energy metabolism (Yu et al, 1995 ), thereby impairing the ability to provide adequate energy for axons.…”
Section: Discussionmentioning
confidence: 88%
“…It is also interesting to note that a recent study has demonstrated that glucose rescued cultured rat retinal cells from rotenone-induced toxicity via both the pentose phosphate pathway and the glycolytic pathway, with the maintenance of ATP levels and reduced reactive oxygen species production (Han et al, 2013 ). On the other hand, we previously found that astrocytes in the optic nerve were activated after TNF injection (Kojima et al, 2012 ). Therefore, one hypothesis is that TNF enhances glucose utilization by astrocytes and can perturb their energy metabolism (Yu et al, 1995 ), thereby impairing the ability to provide adequate energy for axons.…”
Section: Discussionmentioning
confidence: 88%
“…Increased expression of GFAP induced by TNF tended to be suppressed by tacrolimus. Intravitreal injection of TNF may lead to activation of microglia and astrocytes in optic nerve [ 18 , 33 ]. Therefore, it is reasonable to speculate that tacrolimus suppresses the activation of glial cells and inhibits the positive feedback loop among activated glia, cytokines and CaN/NFAT [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…One day after the intravitreal injection of H2B, membrane proteins were extracted from retinal cell lysis with a subcellular proteome extraction kit (Calbiochem, Darmastadt, Germany) according to the manufacturer's instructions. Immunoprecipitation was carried out with the Immunoprecipitation Starter Pack (GE Healthcare Bio-Sciences AB, Uppsala, Sweden), as described previously [22]. The supernatants were incubated with a TLR4 antibody (Santa Cruz Biotechnology, Santa Cruz, CA).…”
Section: Immunoprecipitationmentioning
confidence: 99%